2017
DOI: 10.18632/oncotarget.21924
|View full text |Cite
|
Sign up to set email alerts
|

An NGS-based approach for the identification of sex-specific markers in snakehead (Channa argus)

Abstract: We described a next generation sequencing (NGS)-based approach to identify sex-specific markers and subsequently determine whether a species has male or female heterogamety. To test the accuracy of this technique, we examined the snakehead (Channa argus), which is economically important freshwater fish in China. Males grow faster than females, and there is significant interest in developing methods to skew breeding towards all-males to increase biomass yields. NGS was conducted on DNAs of individual female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…Generally, the genetic system of sex determination for a species could be uncovered through descent identification or karyotype analysis ( Malecha et al, 1992 ; Ortega et al, 2017 ). Presently, high-throughput sequencing has been used as a rapid and efficient way to uncover the sex determination system of an organism ( Pan et al, 2015 ; Ou et al, 2017 ; Shi X. et al, 2018 ; Gao et al, 2019 ; Yang et al, 2020 ). P. clarkii lacks visual heterogeneity chromosomes ( Shi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the genetic system of sex determination for a species could be uncovered through descent identification or karyotype analysis ( Malecha et al, 1992 ; Ortega et al, 2017 ). Presently, high-throughput sequencing has been used as a rapid and efficient way to uncover the sex determination system of an organism ( Pan et al, 2015 ; Ou et al, 2017 ; Shi X. et al, 2018 ; Gao et al, 2019 ; Yang et al, 2020 ). P. clarkii lacks visual heterogeneity chromosomes ( Shi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies designed three set of primers on a MSR which identified males with a success rate of 100%. Similar PCR protocols based on sex-specific markers have been developed for other fish species, for instance in the carps Hypophthalmichthys nobilis, Hypophthalmichthys molitrix (Liu et al, 2018) and the snakehead Channa argus (Ou et al, 2017). However, all these methods were based on end-point PCR, which does not enable the simultaneous detection of multiple genes and requires tissue samples for DNA extraction, affecting the desired non-invasive attribute.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain candidate, specific DNA sequences on the W chromosome of T. tambra for use as a sex marker, we applied an NGS-based approach as previously proposed by Ou et al [32] . Briefly, we first mapped DNA sequences against the reference genome by aligning raw sequence reads from female fish to the male draft assembly with the BWA tool [20] , [21] .…”
Section: Methodsmentioning
confidence: 99%